Reactivity of the metalloligand [Pt2(µ-S)2(PPh3)4] toward tellurium(II) thiourea complexes: synthesis and structural characterization of the ditellurium(I) derivative [{Pt2(µ-S)2(PPh3)4}2Te2]2+ - Fortney-Zirker, Ryland G.; Henderson, William; Lane, Joseph R.; Tiekink, Edward R. T. * (Taylor & Francis, 2018)
Reaction of the platinum(II) sulfide metalloligand [Pt2(µ-S)2(PPh3)4] with the tellurium(II) source TeCl2(tu)2 (tu = thiourea) is dependent on reaction conditions employed. In the presence of added acid, the dominant species observed in the electrospray ionization (ESI) mass spectrum is the tetraplatinum species [{Pt2(µ-S)2(PPh3)4}2Te2]2+. This contains the Te22+ moiety and is related to the previously reported tellurium(I) dithiophosphinate analog [(Ph2PS2)2Te2]. However, in the absence of acid, considerable degradation of the Pt2S2 metalloligand occurs as evidenced by the formation of the mononuclear complex [Pt{SC(NH2)NH}(PPh3)2]+ containing a deprotonated thiourea ligand, together with other thiourea-containing ions, identified by ESI MS. Likewise, attempted use of a fully substituted thiourea, viz. Me2NC(S)NMe2 (tmtu) in TeCl2(tmtu)2, also resulted in degradation of the Pt2S2 core and detection of the known complex [(Ph3P)2PtCl{SC(NMe2)2}]+. The [{Pt2(µ-S)2(PPh3)4}2Te2]2+ cation was isolated with several anions, and unequivocal confirmation of the structure of the complex was obtained by an X-ray structure determination on the BF4- salt, which shows the presence of the Te22+ unit, with the Te–Te bond bridged by two Pt2S2 metalloligands. Density functional theory was used to further probe the Te22+ bonding interactions in [{Pt2(μ-S)2(PPh3)4}2Te2]2+ and the previously reported [(Ph2PS2)2Te2]